2021
DOI: 10.1080/0144929x.2021.1928753
|View full text |Cite
|
Sign up to set email alerts
|

Need frustration in online video games

Abstract: Self-determination theory posits that satisfaction of basic psychological needs is essential for wellbeing. Empirical evidence for the distinction between need frustration and need satisfaction has been growing within the last decade. However, research on player experience of need frustration is lagging behind. This paper investigates whether player experience of need frustration is distinct from need satisfaction in the online video games context. In addition, it examines whether in-game need frustration is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 74 publications
2
32
0
1
Order By: Relevance
“…Consistent with BPNT, participants revealed that their motivation to play the game would drop when they encountered needs-frustrating experiences ( Przybylski et al, 2010 ; Kosa and Uysal, 2021 ). This may manifest when the feeling of agency gets threatened instead of being reaffirmed.…”
Section: Resultsmentioning
confidence: 80%
“…Consistent with BPNT, participants revealed that their motivation to play the game would drop when they encountered needs-frustrating experiences ( Przybylski et al, 2010 ; Kosa and Uysal, 2021 ). This may manifest when the feeling of agency gets threatened instead of being reaffirmed.…”
Section: Resultsmentioning
confidence: 80%
“…If these psychological needs are frustrated a person will experience ill-being. Needs frustration is when needs are actively thwarted and is a separate construct from the absence of needs satisfaction (Chen et al, 2015; Kosa & Uysal, 2021; Vansteenkiste & Ryan, 2013). Table 1 describes the differences between needs satisfaction and needs frustration.…”
Section: Related Literaturementioning
confidence: 99%
“…Kosa and Uysal (2021) are one of the only papers directly investigating needs frustration in video games. They found needs frustration was a strong predictor for escapist motivations, problematic gaming, exit intentions and perceived daily stress (Kosa & Uysal, 2021).…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations